Construction and application of home dietary management program for postoperative patients with preventive ileostomy for rectal cancer - Zhu, Jianhua; Shen, Yuanjuan; Li, Juyun; Wang, Sainan; Shang, Wenjuan; Sun, Min (Frontiers in Nutrition, 2025)
BackgroundRectal cancer is a highly prevalent malignant tumor, and surgery is one of the main treatment methods. Although preventive ileostomy can reduce postoperative complications, it is also prone to cause malnutrition and other problems.ObjectiveTo construct and validate an early postoperative home dietary management program for patients with preventive ileostomy for rectal cancer, aiming to improve their nutritional status and mitigate clinical ileostomy complications.MethodsAn evidence-based dietary management program was developed, covering dietary transition, nutrient intake, and fluid management. A non-concurrent controlled study was conducted with 66 patients at the Affiliated Hospital of Nanjing University of Chinese Medicine. The intervention group received personalized one-on-one dietary guidance (including pre-discharge assessment of dietary habits, individualized meal planning, and weekly WeChat-based follow-up for food diary reviews) in addition to routine health education, while the control group received routine education only.ResultsAt 1 month postoperatively, the intervention group showed significantly better outcomes than the control group in serum albumin (41.00 g/L vs. 38.00 g/L, p = 0.010, r = 0.368), lymphocyte count (1.30 × 10?/L vs. 1.10 × 10?/L, p = 0.009, r = 0.374), and PG-SGA scores (9.85 vs. 10.94, p = 0.037, Cohen's d = 0.525). The intervention group had lower incidences of high-output stoma (HOS; 6.06% vs. 18.18%, OR = 0.29, 95% CI = 0.05–1.56, p = 0.258) and peristomal moisture-associated skin damage (PMASD; 18.18% vs. 24.24%, OR = 0.69, 95% CI = 0.21–2.29, p = 0.547), with positive clinical trends despite no statistical significance.ConclusionThis home dietary management program can effectively improve short-term postoperative nutritional status in patients, and also plays a positive role in reducing the occurrence of HOS and PMASD.